The Impact of Real Options on Willingness to Pay for Investments in Road Safety - Niclas A. Krüger; Mikael Svensson (Örebro University School of Business, 2008)
Abstract: Public investments are dynamic in nature, and decision making must account for the uncertainty, irreversibility and potential for future learning. In this paper we adapt the theory for investment under uncertainty for a public referendum setting and perform the first empirical test to show that estimates of the value of safety (VSL) from stated preference surveys are highly dependent on the inclusion of the option value. Our results indicate an option value of a major economic magnitude. This implies that previously reported VSL estimates are exaggerated.
Keywords: D61; D80; R41; 330; Value of a Statistical Life; Real Options; Contingent Valuation; Road Safety